The Effect of Non-Financial Compensation and Training on Employee Job Satisfaction at PT. Andalaswahana Berjaya - Halimahtussyakdiah, Halimahtussyakdiah; Wiska, Mayroza; Hasibuan, Anggy Qurnia Ra’afi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2024)
This research was conducted to determine the effect of non-financial compensation and training on employee job satisfaction at PT. Andalas Wahana Berjaya (AWB) Dharmasraya Regency in 2024. The analysis method in this research is quantitative, and data is collected using a questionnaire. Data analysis techniques using validity tests, reliability tests, classical assumption tests, multiple linear regression tests, and hypothesis tests. The research sample was 119 permanent employees. The sample in this study was determined using non-probability sampling with the census method. Based on the research results, it can be concluded that non-financial compensation significantly affects the dependent variable, namely employee job satisfaction at PT. Andalas Wahana Berjaya (AWB). Apart from that, there is a significant influence between training variables on employee job satisfaction at PT. Andalas Wahana Berjaya (AWB). Based on the F test, the results show that non-financial compensation (X1) and training (X2) have a significant simultaneous effect on employee job satisfaction (Y) at PT. Andalas Wahana Berjaya (AWB) Dharmasraya Regency in 2024.